Non-Small Cell Lung Cancer: Challenge and Improvement of Immune Drug Resistance - Kong, Fanming; Wang, Ziwei; Liao, Dongying; Zuo, Jinhui; Xie, Hongxia; Li, Xiaojiang; Jia, Yingjie (Frontiers in Oncology, 2021)
Lung cancer is the leading cause of cancer deaths in the world. At present, immunotherapy has made a great breakthrough in lung cancer treatment. A variety of immune checkpoint inhibitors have been applied into clinical practice, including antibodies targeting the programmed cell death-1, programmed cell death-ligand 1, and cytotoxic T-lymphocyte antigen 4, and so on. However, in the actual clinical process, about 30% to 50% of patients still do not receive long-term benefits. Abnormal antigen presentation, functional gene mutation, tumor microenvironment, and other factors can lead to primary or secondary resistance. In this paper, we reviewed the immune mechanism of immune checkpoint inhibitor resistance, various combination strategies and prediction of biomarkers to overcome resistance, in order to accurately screen out the advantageous population, expand the beneficiary population and enable precise and individualized medicine.